Exploring the emerging digital scene in Art History and museum practice - Alexandros Teneketzis (Esboços, 2020)
This article addresses the current digital status in the fields of Museology and History of Art, both in Greece and internationally, in order to examine, record and analyse the extent of usage and the impact of digital tools. We will study the state-of-the-art in the fields of Museology and Art History, with a particular focus on examining the degree to which Greek institutions of culture and arts, as a case study in Europe, use state-of-the-art digital technologies (e.g., semantic technologies, augmented reality, and ubiquitous computing) for (a) storing, managing and documenting artworks together with all relevant knowledge/information; and (b) interpreting and presenting artworks to the public. We will also study and analyse the degree of interrelation between knowledge/information, and art and cultural heritage that is currently hosted in distinct cultural and art institutions around Greece, as well as between Greek institutions and relevant projects abroad. In this context, the issue at stake is the identity and the way Art History is exercised.